Effect of soaking sunflower seeds in different concentrations of sodium chloride and sodium carbonate on germination and seedling viability (Albayan Scientific Journal, 2024)
A laboratory experiment was conducted in the Grain Technology Laboratory, Department of Crops - Faculty of Agriculture - Omar Al-Mukhtar University, to study the effect of different concentrations of sodium chloride salts NaCl and sodium carbonate Na2Co3 on the germination and growth of sunflower seeds. The factorial experiment was conducted using a completely randomized design (RCD) in three replicates, where the treatments were different concentrations of sodium chloride salt NaCl (control, 3000 ppm, and 5000 ppm) and sodium carbonate salt Na2Co3 (control, 3000 ppm, and 5000 ppm) on the germination and growth characteristics of sunflower seedlings (Giza 102). The results showed no significant differences between the salts used in all the studied characteristics. The results showed significant differences between the salt concentrations on all the germination and growth characteristics of sunflower seeds: germination percentage (%), root length (cm), shoot length (cm), seedling wet weight (g), and germination strength coefficient, where the treatment gave Control (distilled water) gave the highest recorded values ​​for all studied traits compared to the lowest values ​​when treated with 5000 ppm. The interaction between sodium chloride and sodium bicarbonate salts and their different concentrations showed significant differences, as the control (distilled water) gave the highest values ​​for all studied traits compared to the lowest recorded values ​​when treated with the two salts (sodium chloride and sodium carbonate) with a concentration of 5000 ppm.
Keywords: sunflower; salinity and alkalinity; germination and growth